Technology Leadership of School Administrators Affecting to Digital Citizenship of Teachers in Basic Education Institution under Surin Primary Educational Service Area Office 3 - Onruang, Mettawat; Khattiyasuwan, Saksit; Chaitong, Supop; Nuttaro, Washrintra; Sansuk, Nonthapoom (Journal for Developing the Social and Community, 2026)
Background and Aims: Digital technology plays a significant role in the lives of people of all ages and its use is increasing. Although most people in society use the internet or various digital media as part of their lives, this research aims to 1) study the technological leadership of school administrators, 2) study the digital citizenship of teachers, 3) study the relationship between the technological leadership of school administrators and the digital citizenship of teachers, and 4) study the impact of the technological leadership of school administrators on the digital citizenship of teachers in schools under the Surin Primary Educational Service Area Office 3. Methodology: This research is a survey study. The sample group consists of 336 teachers from schools under the Surin Primary Educational Service Area Office 3. The sample size was determined using the Krejcie-Morgan table. Stratified random sampling was used, with the district where the school is located as the sampling stratum. The instrument used was a questionnaire with a 5-level Likert scale, with an Index of Content Validity (IOC) of 0.60 - 1.00 and a reliability coefficient of 0.97. The statistics used for data analysis were mean and standard deviation. Pearson correlation coefficient and multiple regression analysis were used to analyze the findings. Results: 1) School administrators exhibited the highest level of technological leadership overall; 2) Teachers demonstrated the highest level of digital citizenship overall; 3) There was a very strong positive correlation (r = 0.92) between school administrators' technological leadership and teachers' digital citizenship (p < .01); and 4) School administrators' technological leadership significantly influenced teachers' digital citizenship (p < .01), predicting 87.40% of the variance. The predictive equation in raw scores is: Y = 0.704 + 0.348X1 + 0.280X4 + 0.218X5. Conclusion: school administrators exhibited the highest level of technological leadership, and teachers also demonstrated the highest level of digital citizenship overall. The technological leadership of school administrators was significantly correlated with and influenced teachers' digital citizenship (p < .01).